Significance and Limitations of Stable Oxygen Isotope Ratios in the Apatite Phosphate of Archaeological Vertebrate Finds for Provenance Analysis in an Alpine Reference Region. (22nd April 2018) - Mauder, M.; Ntoutsi, E.; Kröger, P.; Mayr, C.; Toncala, A.; Hölzl, S.; Grupe, G.
Abstract : A multi‐isotope fingerprint consisting of δ 18 Ophosphate, 87 Sr/ 86 Sr, 208 Pb/ 204 Pb, 207 Pb/ 204 Pb, 206 Pb/ 204 Pb, 208 Pb/ 207 Pb and 206 Pb/ 207 Pb was established in the bioapatite of 219 individual archaeofaunal remains (cattle, pig, red deer) excavated from sites located along a specific transect of the European Alps, namely the Inn–Eisack–Adige–Brenner Passage, that has been of eminent importance since European prehistory. This reference area is vertically stratified, and since δ 18 O in the skeleton is influenced by climate, water source, physiology and even culture, we tested the relative contribution and importance of δ 18 O as a component of the multi‐isotope fingerprint for provenance analysis in this alpine region by a novel mathematical approach. In particular, we adapted a supervised learning approach through expectation–maximization (EM) clustering for fingerprint extraction and evaluated the contribution of each isotopic ratio to the data structure. While an altitude effect was evident in δ 18 O, its overall structural importance in the complete isotopic fingerprint was rather low. Therefore, provenance analysis of bioarchaeological finds in this region is possible by measuring stable Sr and Pb ratios alone, which is of considerable importance when δ 18 O values are not available, e.g., in cremated finds, although some information is lost. Whether this is tolerable depends on the scientific question to be solved.